INHIBITORY EFFECT OF PYRAZOLE DERIVATIVES ON THE P-NITROPHENYL PHOSPHATE PHOSPHATASE ACTIVITY OF ALKALINE PHOSPHATASE: UDC 542.978+577.15.025 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2007)
Inhibition efficiency of the catalytic activity of alkaline phosphatase by novel 3,5-substituents of 1H-pyrazolate was examined. This indicates that among four tested compounds there are competitively and uncompetitively inhibitors. It was shown that magnesium ions do not influence on inhibitor effect.
Keywords: -